Sonographic findings of pinpoint hyperechoic foci in the small intestine, liver, and mesenteric lymph nodes are indicative of canine Heterobilharzia americana infection. Issue 5 (14th June 2020) - Moshnikova, Valentina S.; Gilmour, Lindsey J.; Cook, Audrey K.; Fabiani, Michelle
Abstract: Canine schistosomiasis, caused by the trematode Heterobilharzia americana, can pose a diagnostic challenge due to nonspecific symptoms. The aim of this multicenter, retrospective, descriptive study was to compare the prevalence and extent of sonographic changes associated with schistosomiasis between affected and infection‐free dogs. Medical records of two referral centers were searched for dogs with confirmed schistosomiasis that had undergone an abdominal ultrasound. Fifty‐five cases fulfilled the inclusion criteria, and a contemporaneous control group was derived from dogs that tested negative for H. americana . Two blinded reviewers evaluated the images. The majority of Heterobilharzia ‐infected (further termed H‐pos) dogs (82%) had ultrasonographic abnormalities in the small intestine ± liver. Abnormal layering of the small intestine was noted in 38 of 54 H‐pos dogs, compared to six of 54 control dogs ( P  < .0001). Pinpoint hyperechoic foci were noted in the small intestinal submucosa or muscularis layers in 25 of 54 H‐pos dogs, but only three controls ( P  < .0001). Heterogeneity of the hepatic parenchyma and pinpoint hyperechoic foci were more prevalent in H‐pos dogs (65% vs 40%; P  = .0213 and 44% vs 18%; P  = .0068, respectively). Pinpoint hyperechoic foci within mesenteric lymph nodes were noted in seven H‐pos dogs and none of the controls ( P  = .0128). The combination of heterogeneous small intestine wall layering and pinpoint hyperechoic foci in small intestine, liver, or mesenteric lymph nodes was the most reliable indication of infection ( P  = .0001; odds ratio = 36.87), with positive predictive value of 94%, yet modest sensitivity for the detection of infection (58%). Observing these sonographic features suggests schistosomiasis and should prompt further testing.